Performing arts, intercultural dialogues and socio-legal creation Songs of origin and sacred law - Valcárcel García, Jorge Alberto (Universidad Pedagógica y Tecnológica de Colombia, 2003)
he author invites us to recognize myth and ritual as a synthesis of law, customs and rights. He proposes interdisciplinary work. between the scenic arts and cultural anthropology as a dialogical and experiential exercise in relating with and understanding Colombian Indigenous groups. He also suggests that we listen to ancestral Native American knowledge as a way to continue processes of intercultural dialogue in the search for legal pluralism.